On the Comparison of the Applications of Conventional Ranking Techniques in Determining the Priority Factors Affecting Seed Production of Medicinal Plants: Case of Guilan Province, Iran - Sepideh Gholinezhad (International Journal of Agricultural Management and Development, 2017)
Aimed at identifying and prioritizing promoters and deterrent affecting seed production of medicinal plants, the present study was conducted in 2014. The Delphi method was conducted using a panel of 13 experts in Guilan Natural Resources and Agriculture Organization. In the first round of the study, multiple-response techniques were used for content analysis. Based on the results of the first round, the second round questionnaire was featuring a Likert type scale that was then filled out by the first round respondents. Next, by comparing the conventional techniques, data were analyzed for investigation. The use of ranking techniques led largely to the same results or results with slight differences. The study recommends devoting due attention to the technical and environmental conditions such as proper storage, to avoid the wasteful harvesting of seeds at risk, and to provide favorable conditions for the domestication of medicinal plants. In addition, the role of research, training, and information dissemination of the economic benefits would receive high importance. Furthermore, designing and implementing a legal monitoring mechanism and an active and comprehensive policy making process, as well as providing facilities and equipment necessary for the preparation, cultivation, and harvest of seeds by decision-making, executive institutions, and organizations would notably be effective to tackle the present challenges.